Pseudo Tumour Cerebi (Benign Intracranial Hyprtension) - Khan, Muhammad Tariq (Journal of Postgraduate Medical Institute, 2011)
It is a condition where there is raised intracranial pressure unrelated to tumour, hydrocephalus or frank brain edema. The term Benign Intracranial Hypertension (BIH) is a misnomer. The presenting symptoms are usually headaches, nausea, vomiting, dizziness and visual dysfunction.